Temporal variability in the trophic composition of benthic invertebrates in the Indian Sub-Antarctic Ocean. (September 2020) - Puccinelli, Eleonora; Smart, Sandi M.; Fawcett, Sarah E.
Abstract: Food availability is a primary factor determining species distribution and success, especially for offshore benthic organisms that rely on sinking particles as their main food supply. Temporal changes in the quantity and quality of food sources, often linked to shifts in the prevailing hydrographic conditions, thus have important consequences for benthic community composition and ecosystem functioning. Here, we investigate variability in the biochemical composition of offshore benthic organisms and their food sources across different time-scales (3 weeks, 1 year, 2 years) at the Sub-Antarctic Prince Edward Islands (PEIs) using nitrogen and carbon stable isotope (SI; δ 15 N and δ 13 C, respectively) and fatty acid (FA) analyses. The δ 15 N of suspended particulate matter (SPM) did not show a consistent trend over time, probably because the primary driver of δ 15 NSPM variability appears to be seasonality and we sampled at roughly the same time each year. In contrast, the δ 13 CSPM increased with time, likely as a result of the changing proportion of macroalgal detritus relative to offshore phytoplankton biomass. The δ 15 N and δ 13 C of select trophic groups varied with time, but not necessarily in synchrony with the SPM, possibly due to differences in the SI turnover rates of the food sources versus the consumers. In contrast, the FA composition of most taxa did change over time, reflecting the shorter integration period for FA compared to SI. While taxa showed different FA patterns across the time-scales investigated, the dominant trend was one of decreasing food quality with time. Combined, the SI and FA results indicate that the response of the benthos to the factor Time is not straightforward. We conclude that the two techniques provide different yet complementary temporal information, with animal SI ratios reflecting the longer-term and FA composition the shorter-term response of the benthos to changing food availability. Our findings suggest that different species at the PEIs will respond differently to climate-driven changes in food quality and quantity, increasing the uncertainty facing this vulnerable ecosystem. Highlights: Temporal variation in the diet of benthos was investigated at Sub-Antarctic islands. The δ 13 C of suspended material varied with time but its δ 15 N did not. Trophic groups had different responses to the factor Time. Organismal fatty acid composition indicates decreasing food quality with time. Benthos may have complex responses to long-term changes at the islands.